2007
DOI: 10.1529/biophysj.106.094474
|View full text |Cite
|
Sign up to set email alerts
|

Tectorial Membrane Stiffness Gradients

Abstract: The mammalian inner ear processes sound with high sensitivity and fine resolution over a wide frequency range. The underlying mechanism for this remarkable ability is the "cochlear amplifier", which operates by modifying cochlear micromechanics. However, it is largely unknown how the cochlea implements this modification. Although gradual improvements in experimental techniques have yielded ever-better descriptions of gross basilar membrane vibration, the internal workings of the organ of Corti and of the tecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
78
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(92 citation statements)
references
References 43 publications
10
78
2
2
Order By: Relevance
“…Whereas von Békésy (1953Békésy ( , 1960 and Shoelson et al (2004) found no systematic longitudinal stiffness changes in the TM, a systematic change in driving point stiffness measured at the TM has been reported by our group in the gerbil (Emadi et al 2002;Richter et al 2007) and by Gueta at al. (Gueta et al 2006 in the mouse.…”
Section: Tectorial Membranementioning
confidence: 43%
See 4 more Smart Citations
“…Whereas von Békésy (1953Békésy ( , 1960 and Shoelson et al (2004) found no systematic longitudinal stiffness changes in the TM, a systematic change in driving point stiffness measured at the TM has been reported by our group in the gerbil (Emadi et al 2002;Richter et al 2007) and by Gueta at al. (Gueta et al 2006 in the mouse.…”
Section: Tectorial Membranementioning
confidence: 43%
“…Furthermore, stiffness measurements were made on isolated TM (Freeman et al 2003a, b;Gueta et al 2006Gueta et al , 2008Gueta et al , 2011Shoelson et al 2004), in vitro (Emadi et al 2002Richter et al 2007;von Békésy, 1960) and in vivo (Zwislocki and Cefaratti 1989;Zwislocki et al 1988). Some experimental sets were obtained from different sites along the cochlea, and a longitudinal gradient could be determined (Emadi et al 2002(Emadi et al , 2004Gueta et al 2006Gueta et al , 2011Richter et al 2007;von Békésy, 1960).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations